Factors Related to Treatment Adherence in Older Persons with Hypertension - Samdaengsarn, Dalima; Chinnawong, Tippamas; Thaniwatthananon, Ploenpit (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
This descriptive research aimed to identify factors related to treatment adherence in older persons with hypertension. The samples were 197 older persons with hypertension receiving care at the out patient clinic, Maharaj Nakhon Si Thammarat Hospital, during February to May 2017. Research instruments used for data collection were questionnaires consist of 5 parts: 1) Personal information, 2) Health information and access to health service, 3) Social support, 4) Perceived severity and risk of complications from hypertension, and 5) Treatment adherence to hypertension. The reliability of instruments part 2-5 were tested using Cronbach’s alpha coefficient, showed 0.81, 0.82, 0.85, and 0.85 respectively. The statistics used for data analysis were percentage, mean, standard deviation, Chi-Square, and Pearson’s product moment correlation coefficient. The test statistic is statistically significant at the .05 level. The result revealed the following: 1) Treatment adherence to hypertension of older persons with hypertension was at a high level (M = 1.63, SD = .29). 2) Occupation, marital status and social support were related to treatment adherence in older persons with hypertension significantly ( 2 = 4.77, p < .05, 2 = 5.34, p < .05 and r = .27, p < .01 respectively). However, education, access to health services, illness duration and severity of illness were not related to treatment adherence in older persons with hypertension The results of this study can be used as a basis data for encouraging of family and social support in older persons with hypertension to maintain treatment adherence.